Colour generation for optically driving liquid crystal display. Issue 12 (25th September 2020) - Ma, Ying; Xin, Sang Jing; Liu, Xiaoyu; Liu, Yang; Sun, Jiatong; Wang, Xiaoqian; Guo, Qi; Chigrinov, Vladimir G.
ABSTRACT: The optically driving liquid crystal displays (ODLCDs), by changing the easy axis of liquid crystal molecules under exposure light, are exploited in many display devices requiring ultra-low consumption. In this manuscript, we propose foldable and bendable colour ODLCDs lacking electronics and common back light. Two techniques to realise colour ODLCDs are discussed using colour filter and reflective paint as colour array sector. With these two approaches, we are able to produce three-primary-colour (red, green and blue) display with 21% NTSC colour triangle. In addition, a high-resolution colour display can be achieved through improving resolution of colour array sector. GRAPHICAL ABSTRACT: uf0001